2021
DOI: 10.1002/cne.25254
|View full text |Cite
|
Sign up to set email alerts
|

Morphological principles of neuronal mitochondria

Abstract: In the highly dynamic metabolic landscape of a neuron, mitochondrial membrane architectures can provide critical insight into the unique energy balance of the cell. Current theoretical calculations of functional outputs like adenosine triphosphate and heat often represent mitochondria as idealized geometries, and therefore, can miscalculate the metabolic fluxes. To analyze mitochondrial morphology in neurons of mouse cerebellum neuropil, 3D tracings of complete synaptic and axonal mitochondria were constructed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…The pera membrane density in these sulfate-reducing bacteria ( Fig. 6E ) was 5 to 10 times lower than that typically observed for metazoan crista membrane density ( 44 47 ). This lower density can be attributed to the finding that either the pera did not extend far into the interior, as was typical for the T3B1 pera ( Fig.…”
Section: Discussionmentioning
confidence: 51%
“…The pera membrane density in these sulfate-reducing bacteria ( Fig. 6E ) was 5 to 10 times lower than that typically observed for metazoan crista membrane density ( 44 47 ). This lower density can be attributed to the finding that either the pera did not extend far into the interior, as was typical for the T3B1 pera ( Fig.…”
Section: Discussionmentioning
confidence: 51%
“…The IMM is just one example of a highly curved membrane in cells; others include narrow tubules in the peripheral ER 126 and rims of Golgi cisternae 127 . A common feature across these organelles is that regions of very high curvature are present alongside those with low curvatures 7,128,129 . While relevant curvature-inducing proteins have been identified in these structures, how bimodal distributions of curvature are stabilized within the same continuous lipid membrane is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Further, globular shaped mitochondria could also be a favorable adaptation as it is recently shown that, in comparison to elongated mitochondria, globular mitochondria contain densely packed cristae membranes with high curvature. As ATP synthase is known to localize at intense curvature in cristae, globular mitochondria might possess better energetic capabilities [83,84]. Further ultrastructural analysis along with mitochondrial activity assays may shed light on this possibility.…”
Section: Plos Geneticsmentioning
confidence: 99%